MANAJEMEN TIM KERJA LITURGI DALAM MENDORONG PARTISIPASI AKTIF UMAT BERIMAN DI PAROKI RENYA ROSARI DERI - Ayus Ratrigis (Sekolah Tinggi Kateketik dan Pastoral Rantepao (STIKPAR) Toraja, 2022)
The presence of the liturgical work team provides great assistance to the liturgical services in the Church. Through the liturgical work team, the faithful are helped to give active participation in doing liturgy. The Covid-19 pandemic was a concrete challenge that the faithful faced to participate actively in the Church. Various liturgical activities were carried out online. Moreover, at Renya Rosari Deri Parish, liturgical activities had been abolished. Furthermore, the use of the new Order of Mass made it difficult for the faithful to be actively participated in the Eucharist. Through a qualitative research, researcher found that in this situation the management function of the liturgical work team needs to be improved. Some of the pastoral steps that can be carried out through the management function are holding liturgical and sacramental catechesis, making the faithful to take part in liturgical services, and initiating liturgical inculturations.